Students' Points of View on the Execution of Visual Media in Indonesian Dialect Instruction for Review 6 at SDN Cibalung 04, Cimanggu - Muhammad Rizqi Siregar; Sriyanto Sriyanto (Proceedings Series on Social Sciences & Humanities, 2025)
This investigate explores the viewpoints of sixth-grade understudies with respect to the integration of visual media—specifically images—into Indonesian dialect instruction at SDN Cibalung 04, Cimanggu. Visual media is recognized as a capable instructive instrument that can essentially upgrade understudy engagement and comprehension, especially inside dialect learning settings. Utilizing a graphic subjective technique, information were accumulated through classroom perception, semi-structured interviews, and survey dissemination among the understudies. The comes about demonstrate that most understudies reacted favorably to the utilize of picture-based media. They detailed superior comprehension of perusing materials, expanded eagerness amid lessons, and more noteworthy interest in classroom intelligent. Moreover, visuals were seen to back memory maintenance of the substance instructed. In light of these discoveries, it is proposed that teachers proceed to utilize picture media as an inventive and compelling educating methodology to assist boost scholarly execution.